Comparative study of the levonorgestrel intrauterine system and laparoscopic hysterectomy for the treatment of heavy menstrual bleeding in enlarged uteri - Daniella De Batista Depes; Marcos Vinícius Maia da Mata; Ana Maria Gomes Pereira; João Alfredo Martins; Maíta Poli de Araújo; Reginaldo Guedes Coelho Lopes; Zsuzsanna Ilona Katalin de Jármy-Di Bella (Einstein (São Paulo), 2023)
ABSTRACT Objective To evaluate the effectiveness of the levonorgestrel intrauterine system in the treatment of patients with heavy menstrual bleeding and an enlarged uterus and to compare satisfaction and its complications with hysterectomy. Methods This was a comparative cross-sectional observational study of women with heavy menstrual bleeding and an enlarged uterus. Sixty-two women were treated and followed up for four years. Insertion of the levonorgestrel intrauterine system was performed in Group 1, and laparoscopic hysterectomy was performed in Group 2. Results In Group 1 (n=31), 21 patients (67.7%) showed improvement in the bleeding pattern, and 11 patients (35.5%) had amenorrhea. Five patients (16.1%) remained with heavy bleeding and were considered to have experienced treatment failure. There were seven expulsions (22.6%); in five patients, bleeding remained heavy, but in two patients the bleeding returned to that of normal menstruation. No relationship was found between treatment failure and greater hysterometries (p=0.40) or greater uterine volumes (p=0.50), whereas expulsion was greater in uteri with smaller hysterometries (p=0.04). There were 13 (21%) complications, seven (53.8%) in the group that underwent insertion of the levonorgestrel intrauterine system (all were device expulsions), and six (46.2%) in the surgical group, which were the most severe ones (p=0.76). Regarding satisfaction, 12 patients (38.7%) were dissatisfied with the levonorgestrel intrauterine system and one (3.23%) was dissatisfied with the surgical treatment (p=0.00). Conclusion Treatment with the levonorgestrel intrauterine system in patients with heavy menstrual bleeding and an enlarged uterus was effective, and when compared with laparoscopic hysterectomy, it had a lower rate of satisfaction and the same rate of complications, although less severe.